2021
DOI: 10.1108/ijesm-02-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Shock and volatility spillovers between oil and emerging seven stock markets

Abstract: Purpose This study aims to examine the volatility spillover effects between oil and stock returns in the emerging seven economies. Design/methodology/approach In this study, the Granger causality test and vector autoregression-generalized autoregressive conditional heteroskedasticity approach to analyze the volatility spillover from 1995 to 2019 were used. The findings provide evidence of significant volatility spillover between oil and Brazil, China, India, Indonesia, Mexico, Russia and Turkey (E7) stock ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
7
1
2
Order By: Relevance
“…Gomes and Chaibi (2014) find mixed results for 23 stock markets, but the spillovers run more often from oil to stock markets. Other recent studies find unilateral shock and volatility spillover from oil price to stock market returns (Anan et al, 2014;Bouri, 2015;Amed, 2017;Kurshid and Uludag, 2017;Uludag and Safarzadeh, 2018;and Chen et al, 2018). These studies find unilateral transmission for India, Lebanon, Egypt, some Balkan stock markets, and China.…”
Section: Introductionmentioning
confidence: 92%
“…Gomes and Chaibi (2014) find mixed results for 23 stock markets, but the spillovers run more often from oil to stock markets. Other recent studies find unilateral shock and volatility spillover from oil price to stock market returns (Anan et al, 2014;Bouri, 2015;Amed, 2017;Kurshid and Uludag, 2017;Uludag and Safarzadeh, 2018;and Chen et al, 2018). These studies find unilateral transmission for India, Lebanon, Egypt, some Balkan stock markets, and China.…”
Section: Introductionmentioning
confidence: 92%
“…Te international stock market plays an important role in the fnancial system. One strand of the literature on the connectedness within the international stock market focuses on the transmission between two important countries [6][7][8][9][10], the connectivity among countries participating in international organizations such as the G7 [11][12][13], and the dependence between the stock market and other markets, such as exchange markets [14,15], the crude oil market [16][17][18], markets for other commodities [19][20][21], and cryptocurrencies [22][23][24]. Prior works adopt the GARCH family model, the VAR model, and the Copula model to analyze the time-varying correlations between fnancial markets, and they emphasize the efects of policy factors (e.g., changes in monetary policy or regime) and national economy factors (e.g., fnancial and trade linkages) on connectedness among stock markets.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature has discussed the volatility spillover from energy consumption to stock markets in developed and developing countries [8][9][10][11][12][13][14]. e primary study in this regard was stepped by Hamilton [15] by focused on the impact of oil prices on the economy of the U.S. and found that sharp fluctuation in oil prices has a significant impact on the economy.…”
Section: Introductionmentioning
confidence: 99%
“…After examining all these studies, a mixed conclusion can be drawn because some studies suggest that the volatility is transmitted from the oil market to the stock markets of different countries; on the other hand, some studies prove that there is no transmittal of volatility from the market of oil to the stock of different countries. e findings vary from country to country and analyzed periods [17][18][19][20][21]. is difference in findings may be due to the methodology, model, time, or data set.…”
Section: Introductionmentioning
confidence: 99%